Visions of Beatitude in Santa Maria Novella's Paradise: The Ultimate Goal of Human Endeavor in Monastic Traditions and Dominican Thought - Munk, Ana (2013)
The article examines the development of the doctrine of beatitude in medieval visual arts from 12th to 14th centuries. It focuses on the theology of Paradise, the medieval development of the doctrine and its Dominican interpretation in visual arts of Italian trecento.
ENG